The effect of injurious compression on the elastic, hyper-elastic and visco-elastic properties of porcine peripheral nerves. (September 2021) - Fraser, Susan; Barberio, Carla G.; Chaudhry, Tahseen; Power, Dominic M.; Tan, Simon; Lawless, Bernard M.; Espino, Daniel M.
Abstract: The aim of this study was to characterise the viscoelastic and hyper-elastic properties of the ulnar nerve before and after compression has been induced, in order to aid the understanding of how the mechanical properties of nerves are altered during nerve compression, a contributing factor to cubital tunnel syndrome. Ulnar nerves were dissected from porcine legs and tensile tested to 10% strain. The Young's modulus and Yeoh hyper-elastic model were used to evaluate the materials elastic and hyper-elastic properties respectively. Dynamic mechanical analysis (DMA) was used to evaluate the viscoelastic properties over a range of frequencies between 0.5 Hz and 38 Hz. The nerves were then compressed to 40% for 60 s and the same tests were carried out after compression. The nerves were stiffer after compression, the mean Young's modulus before was 0.181 MPa and increased to 0.601 MPa after compression. The mean shear modulus calculated from the Yeoh hyper-elastic model was also higher after compression increasing from 5 kPa to 7 kPa. After compression, these properties had significantly increased ( p  < 0.05). The DMA results showed that the nerves exhibit frequency dependent viscoelastic behaviour across all tested frequencies. The median values of storage modulus before compression ranged between 0.605 and 0.757 MPa across the frequencies and after compression between 1.161 MPa and 1.381 MPa. There was a larger range of median values for loss modulus, before compression, median values ranged between 0.073 MPa and 0.216 MPa and after compression from 0.165 MPa to 0.410 MPa. There was a significant increase in both storage and loss modulus after compression ( p  < 0.05). The mechanical properties of the nerve change following compression, however the response to decompression in vivo requires further evaluation to determine whether the observed changes persist, which may have implications for clinical recovery after surgical decompression in entrapment neuropathy.